2015
DOI: 10.5812/ircmj.17(4)2015.26321
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Regular Aerobic Exercise on Reverse Cholesterol Transport A1 and Apo Lipoprotein A-I Gene Expression in Inactive Women

Abstract: Background:Atherosclerotic cardiovascular disease is currently a cause of mortality in some parts of the world. The ATP-Binding Cassette Transporter (ABCA1) gene prepares instructions to produce the ATP-binding cassette transporter protein whose operation is for export of phospholipids and cholesterol, outside cells where they are limited to Apolipoprotein A1 (apoA1). Increased ABCA1 activity could inhibit atherosclerosis.Objectives:In the present study, the effect of aerobic exercise was investigated on gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Study found that the ABCA1 gene expression was significantly different before and after exercise [69]. Ghanbari-Niaki et al [70] also found that ABCA1 mRNA expression increased regardless of the intensity of exercise. Therefore, they hypothesized that aerobic exercise may increase the expression of ABCA1 to exert its role in reducing cardiovascular risk.…”
Section: Aerobic Exercise With Lipids and Lipoproteinsmentioning
confidence: 99%
“…Study found that the ABCA1 gene expression was significantly different before and after exercise [69]. Ghanbari-Niaki et al [70] also found that ABCA1 mRNA expression increased regardless of the intensity of exercise. Therefore, they hypothesized that aerobic exercise may increase the expression of ABCA1 to exert its role in reducing cardiovascular risk.…”
Section: Aerobic Exercise With Lipids and Lipoproteinsmentioning
confidence: 99%
“…Indeed, studies suggest that altering the cardiac expression of specific ABC transporters can significantly alter the rate of DOX clearance from the heart (Dell'Acqua et al, 1999;van Asperen et al, 1999). In addition, the expression of several different ABC transporters has been demonstrated to be upregulated in response to exercise training (Tofighi et al, 2015). Therefore, an exercise-induced increase in the expression of ABC transport proteins may be responsible for the protective effects of exercise on the heart.…”
Section: Introductionmentioning
confidence: 99%
“…However, exercise‐regulated cellular cholesterol efflux might depend on the different doses of aerobic exercise. Habitual aerobic exercise can increase cellular ABCA1 gene expression 20,21 . A higher ABCA1 expression was observed in low to moderate circuit‐resistance exercises than in high‐resistance exercise 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Exercise has benefits in terms of reducing cardiovascular risk 19 . High levels of habitual exercise are associated with high ABCA1 expression in human leucocytes 20,21 . A single session of circuit resistance exercise increases ABCA1 expression in peripheral blood lymphocytes 22 .…”
Section: Introductionmentioning
confidence: 99%